The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s00468-002-0230-2
|View full text |Cite
|
Sign up to set email alerts
|

Dendroecological investigations on Swietenia macrophylla King and Cedrela odorata L. (Meliaceae) in the central Amazon

Abstract: The width of the increment zones in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
75
2
14

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 32 publications
10
75
2
14
Order By: Relevance
“…ANNUAL DIAMETER GROWTH PATTERNS.-Mean annual Swietenia diameter growth increment increased predictably with total annual (July-June) rainfall and with rainfall totals during the first half of the growing season at Marajoara. This finding corroborates results from field studies in Mexico, Belize, and southwestern Amazonia showing that diameter growth rates by Swietenia increase with annual precipitation totals (Whigham et al 1998, Dünisch et al 2003, Shono & Snook 2006. Our data suggest that rainy season duration influences annual growth patterns more than total precipitation, that is, whether wet season onset occurs in September vs. October or even late November.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…ANNUAL DIAMETER GROWTH PATTERNS.-Mean annual Swietenia diameter growth increment increased predictably with total annual (July-June) rainfall and with rainfall totals during the first half of the growing season at Marajoara. This finding corroborates results from field studies in Mexico, Belize, and southwestern Amazonia showing that diameter growth rates by Swietenia increase with annual precipitation totals (Whigham et al 1998, Dünisch et al 2003, Shono & Snook 2006. Our data suggest that rainy season duration influences annual growth patterns more than total precipitation, that is, whether wet season onset occurs in September vs. October or even late November.…”
Section: Discussionsupporting
confidence: 87%
“…Successive drought years lowering phreatic water below average dry season levels can retard wet season recharge and exacerbate mortality in low-ground areas at the study site (Grogan & Galvão 2006). Studies demonstrating that shallow-rooting species are more sensitive to rainfall patterns (Noldt et al 2001, Dünisch et al 2003) support results reported here for Swietenia. This study's second deciduous species, Parkia, demonstrated quite different stem behavior with respect to annual rainfall totals, tending to grow more robustly during years with lower rainfall.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, interannual variation in ring width of C. odorata is related to March-May precipitation during the previous growing season. No relationships between variations in temperature and radial growth of these species were reported (Dünisch et al 2003).…”
Section: Discussionmentioning
confidence: 93%
“…The formation of fewer subannual rings, specially over the recent period, could be due to the age of the trees: older trees have lower rates of intra-annual structure formation (Dünisch, Ribeiro Montóia, & Bauch, 2003); stand/crown position: trees under suppressed growth conditions tend to form more intra-annual structures (Groenendijk et al, 2014); and/or physiological factors as root depth or less susceptibility to insect attacks (Copenheaver, Pokorski, Currie, & Abrams, 2006). Our results imply some important limitation to use the P. copaifera ring-width chronology for reconstructing the climate along the low Atrato River.…”
Section: Discussionmentioning
confidence: 99%